Socialization and Early Detection of Breast Cancer Using the Android Application “MamoApp” - Yuly Peristiowati; Hariyono; Arantrinita (Journal of Community Engagement in Health, 2024)
Cancer is a public health problem in Indonesia with a prevalence of 136.2/100,000 population. One of the most common cancers, especially in women, is breast cancer. The highest incidence of breast cancer in women is 42.1 per 100,000 population with an average death rate of 17 per 100,000 population. One of the countermeasures for breast cancer is case finding with early detection carried out through clinical breast examination (CBE) and breast self-examination (SADARI).  One of the features developed by Postgraduate students of the Institute of Health Sciences STRADA Indonesia is a breast cancer early detection application called “MamoApp”. In this community service activity, 2 aspects of activities will be carried out in the Dharma Wanita group of DLHKP office in Kediri city. The first activity is to conduct a socialization in the form of providing health counseling to the Dharma Wanita group about SADARI techniques, the second activity will be carried out early detection of breast cancer using the MamoApp android application. Mamoapp application contains an educational video on awareness examination, then respondents fill out a questionnaire to detect the presence or absence of symptoms of breast cancer, the time used for filling in is approximately 10 minutes. From the results of filling out the questionnaire through the MamoApp application, we will immediately know the conclusion of the examination results, namely: “Indicated Cancer” or ‘Not Indicated Cancer’, so that participants can immediately find out whether the person concerned is indicated by breast cancer or not.  From the results of the questionnaire of 38 participants, there were 2 participants who indicated breast cancer and 36 participants did not indicate breast cancer. Participants who indicated breast cancer by the facilitator were advised to do a further examination to the doctor for a more detailed examination.